A case report of chronic hepatitis-C genotype 4c infection: Non-specific symptoms can become contextually relevant in clinical diagnosis - Mantha, Kameswara Bharadwaj (Indian Journal of Case Reports, 2024)
Chronic hepatitis C (CHC) infection is one of the leading causes of liver disease worldwide and its early diagnosis is often considered a challenge because of its non-symptomatic presentation until late disease progression stages. We report the case of a 52-year-old, South-Indian male with CHC genotype 4c infection. We start with the patient’s initial presentation 12 weeks before the diagnosis with seemingly non-specific symptoms of pedal edema, purpura, peripheral neuropathy, arthralgia, and recent onset of diabetes mellitus (DM). We then present the employed direct-acting antiviral (DAA) management regimen and the patient’s response over the span of 48 weeks. Correlating with observations from recent literature highlighting CHC’s extra-hepatic role in inducing cryoglobulinemic vasculitis (CV) and pancreatic dysfunction, we discuss some educational perspectives on how CV and DM-related symptoms may sometimes become contextually specific in clinically suspecting, assessing risk, and warranting CHC screening and diagnostic confirmation.